Bibliometric analysis: Research trends of acupuncture treatment to cognitive impairment in recent 15 years - Nie, Chen-Chen; Su, Kai-Qi; Gao, Jing; Song, Xiao-Lei; Lv, Zhuan; Yuan, Jie; Luo, Meng; Ruan, Xiao-Di; Fan, Yong-Fu; Yu, Ming-Yue; Qi, Shi-Kui; Feng, Xiao-Dong (Frontiers in Psychology, 2022)
Objectives: Acupuncture therapy has been used for cognitive impairment-related diseases, however, there are still few studies on the overall trend of acupuncture therapy on cognitive impairment based on bibliometric analysis. The purpose of this study was to explore the research trend of the impact of acupuncture on cognitive impairment in the past 15 years, analyze the research trends and hotspots, and provide new ideas and theoretical basis for future research directions. Methods: From the Web of Science Core Collection (WoSCC), the relevant literature on the treatment of cognitive impairment with acupuncture from 2007 to 2022 was retrieved. Then, based on the Citespace and VOSviewer software of the Java platform, the cooperation between countries and institutions in this field, the co-citation of journals and documents, and the cooperation between authors and authors, etc. were analyzed; In addition, the co-occurrence and burst analysis of keywords are also carried out, and a visual knowledge map is drawn. Results: As of August 08, 2022, a total of 394 records related to the treatment of cognitive impairment with acupuncture were identified. The analysis results show: The number and rate of annual publications have steadily increased, with some fluctuations from year to year. The countries that contribute the most to this field are China and the USA. Among them, Beijing University of Chinese Medicine and Capital Medical University are tied for first place in terms of the number of published papers. Tao Jing is the most prolific author and the number one cited author. The most recent keywords are cognitive impairment, memory, Alzheimer’s disease, protocol, systematic reviews, etc. Conclusions: The number of publications on acupuncture for cognitive impairment is expected to increase rapidly in future research, suggesting a bright future for the field. Future research hotspots will focus on acupuncture and electroacupuncture in the treatment of neurological diseases and neurodegenerative diseases, such as cognitive impairment and Alzheimer’s disease, and so on. It is also necessary to strengthen cross-regional and cross-country cooperation among various academic groups.